2D Solitons in P T -Symmetric Photonic Lattices - Muniz, Andre L. M.; Wimmer, Martin; Bisianov, Arstan; Peschel, Ulf; Morandotti, Roberto; Jung, Pawel S.; Christodoulides, Demetrios N. (Physical Review Letters, 2019)
Over the last few years, parity-time (PT) symmetry has been the focus of considerable attention. Ever since, pseudo-Hermitian notions have permeated a number of fields ranging from optics to atomic and topological physics, as well as optomechanics, to mention a few. Unlike their Hermitian counterparts, nonconservative systems do not exhibit a priori real eigenvalues and hence unitary evolution. However, once PT symmetry is introduced, such dissipative systems can surprisingly display a real eigenspectrum, thus ensuring energy conservation during evolution. In optics, PT symmetry can be readily established by incorporating, in a balanced way, regions having an equal amount of optical gain and loss. However, thus far, all optical realizations of such PT symmetry have been restricted to a single transverse dimension (1D), such as arrays of optical waveguides or active coupled cavity arrangements. In most cases, only the loss function was modulated - a restrictive aspect that is only appropriate for linear systems. Here, we present an experimental platform for investigating the interplay between PT symmetry and nonlinearity in two-dimensional (2D) environments, where nonlinear localization and soliton formation can be observed. In contrast to typical dissipative solitons, we demonstrate a one-parameter family of soliton solutions that are capable of displaying attributes similar to those encountered in nonlinear conservative arrangements. For high optical powers, this new family of PT solitons tends to collapse on a discrete network - thus giving rise to an amplified, self-accelerating structure.
CRIS-Team Scopus Importer:2023-04-20